Swimming exercise attenuates diabetic myopathy and is associated with histological and mitochondrial changes in pregnant rats (Rattus norvegicus) - Catinelli, Bruna Bologna [UNESP]; Barbosa, Angélica Mércia Pascon [UNESP]; Carr, Aline Medolago [UNESP]; Oliveira, Rafael Guilen de [UNESP]; Alves, Fernanda Cristina Bergamo [UNESP]; Mosele, Franciele [UNESP]; Chies, Agnaldo Bruno; Felisbino, Sérgio Luis [UNESP]; Sobrevia, Luis [UNESP]; Souza Rossignoli, Patrícia de [UNESP]; Rudge, Marilza Vieira Cunha [UNESP]; Group, Diamater Study [UNESP] (Elsevier, 2025)
AIM: Diabetic-induced myopathy (DiM) is reversed by swimming exercise (SE) in diabetic pregnant rats. This study aims to characterise the role of muscle stem cells (MuSCs), mitochondrial adaptations, and inflammation in this process. METHODS: A mild hyperglycaemic pregnant rat model was created by administering 100 mg/kg streptozotocin to Wistar female newborns on the first day of life. In adulthood, after mating, the rats were assigned to either a sedentary or exercise group. The SE protocol involved 60 min of daily swimming, 6 days per week, from gestational day 0 to 20. On gestational day 21, blood samples, rectus abdominis muscle (RAM), and soleus muscle were collected for analysis of fiber type, MuSCs count, mitochondrial adaptations, and inflammation markers. RESULTS: The diabetic group showed a lower number of fast and slow-twitch fibers. SE increased the number of MuSCs, the MuSCs/myonuclei ratio, mitochondrial area, and count, and restored citrate synthase activity. SE also increased the MuSCs/fiber and myonuclei/fiber ratios, as well as the mitochondria number/fiber and mitochondria area/fiber ratios, showing a positive relationship between mitochondrial count and fiber number in the diabetic group. Inflammation analysis revealed no differences in pro-inflammatory marker expression or quantification. CONCLUSION: These results highlight a new combined effect of SE, increasing MuSCs and mitochondrial number and area, as well as restoring citrate synthase activity, suggesting that changes in muscle histology, MuSCs abundance, and mitochondrial adaptations with SE in diabetic animals may be key mechanisms in attenuating RAM DiM in diabetic pregnant rats.